Falah Profit of Sharia Rural Banks in West Sumatra: Impact of Funding and Financing - Kurnia, Rahmat; Maharani, Nur Avivah; Helmalia, Helmalia; Putra, Gusti Dirga Alfakhri; Melzatia, Haura Hazimah (Al-bank: Journal of Islamic Banking and Finance, 2025)
This study aims to examine the influence of funding and financing activities—specifically Mudharabah Savings, Mudharabah Deposits, and buying and selling transactions on the Falah Profit of Sharia Rural Banks (BPRS) in West Sumatra over the period from 2015 to 2023. Employing a descriptive quantitative methodology with panel data regression analysis, secondary data were collected from the official financial reports published on the OJK website, involving a purposive sample of 38 banks. The analysis reveals that both Mudharabah Savings and Mudharabah Deposits have a positive and statistically significant influence on Falah Profit, with regression coefficients indicating that an increase in these funding sources is associated with higher profitability. Conversely, buying and selling activities exhibit a positive but statistically insignificant effect on Falah Profit, suggesting a less direct impact in this context. The combined impact of these variables explains approximately 82.68% of the variation in Falah Profit, illustrating their substantial role in shaping bank performance. These findings imply that strategic enhancement of Mudharabah-based funding mechanisms can effectively boost profitability, contributing to the stability and growth of Sharia banking institutions in the region. The study thus emphasizes the importance of Islamic financial products and funding schemes in driving sustainable bank performance aligned with Sharia principles